Two-photon transitions in few-electron ions in the presence of static electric fields - Jahrsetz, Thorsten; Surzhykov, Andrey (Physica scripta, 2013)
Two-photon transitions in H- and He-like heavy ions in the presence of an external static electric field are explored using a relativistic Greens function approach and an independent particle model. The effects of Stark mixing on angular correlations, spectral distributions and total transition rates are analyzed in detail. Special emphasis is placed on the 2p1/2 → 1s1/2 two-photon transition in H-like ions and the 1s1/22p1/2:23P0 → 1s21/2:11S0 and 1s1/22s1/2:21S0 → 1s21/2:11S0 two-photon transitions in He-like ions.
Gesehen am 19.03.2021